The Association Between Post-Traumatic Stress and Depressive Symptoms Among Older Puerto Ricans in Boston: How Does Loneliness Matter?. (October 2022) - Wang, Kaipeng; Zhang, Anao; Cuevas, Adolfo G.; De Fries, Carson M.; Hinton, Ladson; Falcón, Luis M.
Objectives: To examine the association between post-traumatic stress and depression and whether such an association differs by level of loneliness among older Puerto Ricans. Methods: Data were collected from 304 Puerto Ricans aged 60 and above living in the Greater Boston area who responded to questionnaires. We used ordinary least squares regression to examine the association between post-traumatic stress, loneliness, and depressive symptoms. Results: Post-traumatic stress was significantly associated with higher levels of depression. The association between post-traumatic stress and depression was stronger for those experiencing a higher degree of loneliness. Discussion: In working with older Puerto Ricans experiencing post-traumatic stress, it is important for mental health professionals to incorporate the assessment of loneliness and to prevent and reduce comorbid depression by addressing loneliness through improving social skills, enhancing social support, and reducing maladaptive social cognition.